Scripture and theology: historical and systematic perspectives - Bokedal, Tomas; Jansen, Ludger; Borowski, Michael (Theologische Bibliothek Töpelmann, 2023)
The academic disciplines of Biblical Studies and Systematic Theology were long closely linked to one another. However, in the modern period they became gradually separated which led to increasing subject specialization, but also to a lamentable lacuna within the various branches of Divinity. As the lack of dialogue between Biblical Studies and the various theological disciplines increased, a minority-group of scholars in the past few decades reacted and sought to re-establish the time-honoured bonds between the disciplines. The present volume is part of this intellectual response, with contributions from scholars of various professional and denominational backgrounds. Together, the book's 25 chapters seek to reinvigorate the crucial cross-disciplinary dialogue, involving biblical, narrative, historical, systematic-theological and philosophic-theological perspectives. The book opens the horizon to contemporary research, and fills a lamentable research gap with a number of fresh contributions from scholars in the respective sub-disciplines